Alterations in the expression of EMT‐related proteins claudin‐1, claudin‐4 and claudin‐7, E‐cadherin, TWIST1 and ZEB1 in oral lichen planus. (4th July 2019) - Hämäläinen, Lasse; Soini, Ylermi; Pasonen‐Seppänen, Sanna; Siponen, Maria
Abstract: Background: Oral lichen planus (OLP) is a chronic T‐cell‐mediated inflammatory disease, which is associated with increased risk of developing oral squamous cell carcinoma. Epithelial‐to‐mesenchymal transition is a physiological phenomenon occurring during growth and organogenesis, but it has also an important role in tumorigenesis. In the present work, we studied the expression of known epithelial‐to‐mesenchymal transition markers in oral lichen planus. Methods: In total, 54 oral lichen planus and 22 control samples were analyzed for epithelial‐to‐mesenchymal transition markers. Samples were immunohistochemically stained for claudin‐1, claudin‐4 and claudin‐7, cadherin‐1 (E‐cadherin), Twist‐related protein 1 (TWIST1) and zinc finger E‐box‐binding homeobox 1 (ZEB1). Results: The expression of claudin‐1, claudin‐4 and E‐cadherin was significantly weaker in oral lichen planus epithelium compared to controls ( P < 0.001). The quantity of claudin‐7‐expressing cells ( P < 0.001) and claudin‐7 staining intensity ( P < 0.05) in the stroma was greater in lichen planus than in control samples. TWIST1 and ZEB1 stainings were negative in the epithelium in both lichen planus and controls. The number of TWIST1‐expressing cells in the stroma was higher in lichen planus than in controls ( P < 0.001). There was a statistically significant difference in ZEB1 staining intensity in the stroma between lichen planus and control samples ( P < 0.05). Conclusions: The data indicate that the expression of claudin‐1, claudin‐4 and E‐cadherin is decreased in oral lichen planus. This may lead to disturbance in epithelial tight junctions, cell‐cell connections and epithelial permeability, contributing to oral lichen planus pathogenesis. Based on the present study, the role of TWIST1 and ZEB1 in oral lichen planus remains unclear.